Smart surveillance system for identifying bikers without helmets using deep learning - Hossain, MD. Iqbal; Muhib, Raghib Barkat (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.